GENE-06. THE ONCOHISTONE H3.3K27M DRIVES DIFFUSE INTRINSIC PONTINE GLIOMA INDEPENDENT OF FUNCTIONAL EZH2. (5th November 2018) - Dhar, Swati; Becher, Oren
Abstract: BACKGROUND: Diffuse Intrinsic Pontine Glioma (DIPG) is an incurable childhood brain tumor. Recent studies demonstrate that the replication independent oncohistone H3.3K27M, mutated in 65% of DIPG cases, inhibits Enhancer of zeste homolog 2 (EZH2), the enzymatic component of Polycomb Repressor Complex 2 (PRC2), leading to a global reduction in H3K27me3 levels and gene de-repression. Conflicting data exists supporting both an oncogenic and a tumor suppressor role for EZH2 in cancer. The present work addressed the functional significance of EZH2 and its cross-talk with the mutant histone H3.3K27M, in the context of DIPG pathogenesis. METHODS: Brainstem tumors were established by intracranial injections of NTv-a; EZH2 f/f neonatal pups using Replication Competent Avian Sarcoma leucosis virus long terminal repeat with splice acceptor (RCAS) viruses, expressing PDGF-B p53 shRNA, and RCAS-Cre/Y. Immunohistochemical staining (IHC) for Ki-67, H3K27me3, GFAP, Olig-2 and Nestin were performed on the Discovery ULTRA (Ventana). Cell proliferation assay (BrdU) was performed in neurosphere cultures established from brainstems of NTv-a; EZH2 f/f neonates, using the EZH2 inhibitor, EPZ011989 (1mM, Epizyme) for 5 days. RESULTS: Ezh2 deletion in NTv-a; Ezh2 f/f mice exacerbated DIPG pathogenesis, indicated by a 2.5-fold higher Ki-67 immunostaining (pEzh2deletion in neurospheres from Ntv-a; Ezh2 f/f neonates enhanced cell proliferation as did the addition of EPZ011989. Superimposition of the H3.3K27M mutant histone in this background, significantly shortened tumor latency, with a median survival of 54 days compared to 70 days in H3.3 wild type histone control group (p<0.05) and 50% incidence of Grade IV tumors. These results suggest that H3K27M may be oncogenic even in the absence of EZH2. FUTURE DIRECTIONS: Current studies aim to analyze the genetic and epigenetic landscape of these tumors using RNA-Seq and functional assays to determine whether EZH2 inhibitors will be a viable option for children with DIPG in the clinic.